Current Therapeutic Opportunities for Estrogen Receptor Mutant Breast Cancer - Murugesan Palaniappan (Biomedicines)
Estrogen receptor α (ERα) drives two out of three breast cancers and therefore ERα is a major therapeutic target for ER-positive breast cancer patients. Drugs that inhibit ERα activity or block estrogen synthesis in the body are currently being used in the clinic to treat ER-positive breast cancer and have been quite successful in controlling breast cancer progression for the majority of patients. However, ER-positive breast cancer often becomes resistant to these endocrine therapies, leading to endocrine-resistant metastatic breast cancer, a very aggressive cancer that leads to death. Recent large-scale genomic studies have revealed a series of activating somatic mutations in the ERα gene (ESR1) in endocrine-resistant metastatic breast cancer patients. Of these, Y537S and D538G mutations are found at a much higher rate in patients with metastatic breast cancer. Remarkably, these mutations produce an ERα with much higher transcriptional activity than wild type in the absence of estradiol, and traditional endocrine therapy has poor efficacy against ER mutants. Therefore, the development of new drugs that target ER mutants is an unmet clinical need for endocrine-resistant metastatic breast cancer. This review summarizes the recent preclinical and clinical trials targeting estrogen receptor mutant breast cancer.